Analisis Metode Anodizing Aluminium dengan Variasi Kuat Arus sebagai Material Velg Kendaraan - Nani Mulyaningsih; Muhammad Noor Faishal Zakiy; Ikhwan Taufik (Universitas Muhammadiyah Yogyakarta, 2024)
Aluminum Alloy 6061 is widely used in various engineering applications, including automotive vehicle wheels. The selection of aluminum alloy wheels involves aspects such as corrosion resistance. To enhance corrosion resistance, there are several methods, one of which is anodizing. Anodizing is a process that involves an electrolytic coating process that transforms the surface of aluminum into aluminum oxide (Al2O3), which the main process of aluminum anodizing requires a solution of sulfuric acid, chromic acid, or a mixture of sulfuric acid and oxalic acid. The sulfuric acid used must be concentrated acid, and acid is an oxidizing substance. The thickness of the oxide is approximately twice the thickness of the lost aluminum. The purpose of this research is to determine the characteristic such as surface roughness values, corrosion rates, and changes in morphology in Aluminum 6061 after undergoing anodizing. In this study, various current strengths were used, namely 0.75 Amperes, 1.5 Amperes, 2.25 Amperes, and 3 Amperes. The highest surface roughness value was obtained at 0.447 μm in the third specimen of the 0.75 Ampere variation, while the lowest was 0.075 μm in the first specimen of the 3 Ampere variation. The highest corrosion rate was observed in the 0.75 Ampere variation, with a rate of 17.724004 mpy, and the lowest was 0.0731653 mpy in the 3 Ampere variation. SEM results show that, in general, Aluminum 6061 tends to have a bright gray color, which is a surface that has been coated by cathode.